2012
DOI: 10.1590/s1020-49892012000200007
|View full text |Cite
|
Sign up to set email alerts
|

Iniquidades raciais em saúde bucal no Brasil

Abstract: The results show racial inequity in oral health in Brazil for all the indicators analyzed (caries, tooth loss, pain, and need for prostheses), with greater vulnerability among the black population compared to whites. Contextual factors related to the human development profile, income distribution, and access to health care policies appear to play a key role in describing the vulnerability of populations to oral health problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
1
21

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 24 publications
4
46
1
21
Order By: Relevance
“…These racial inequalities have also been previously identified in oral healthcare services. The use of public healthcare services was different among dark-skinned blacks (56.8%), light-skinned blacks (53.3%), and whites (41.6%) [47], as was also verified in the present study. In the United States, results have also shown that the dark-skinned black population more commonly seeks out public healthcare services, while the white population more often uses private healthcare services, data which has remained unchanged over time [48,49].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These racial inequalities have also been previously identified in oral healthcare services. The use of public healthcare services was different among dark-skinned blacks (56.8%), light-skinned blacks (53.3%), and whites (41.6%) [47], as was also verified in the present study. In the United States, results have also shown that the dark-skinned black population more commonly seeks out public healthcare services, while the white population more often uses private healthcare services, data which has remained unchanged over time [48,49].…”
Section: Discussionsupporting
confidence: 83%
“…In Brazil, even with its universal healthcare system [56], the same barriers relevant to individual income and, consequently, to the payment of healthcare services can be found [25-30,35,47,52,57,58]. The present study, therefore, identified a dose–response gradient for this variable, which reinforces its determination in the use of public healthcare services.…”
Section: Discussionsupporting
confidence: 69%
“…All of the studies were published between 1975 and 2016 [21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81]. Twenty new studies were included in this update [26,27,28,29,31,38,39,40,44,45,…”
Section: Resultsmentioning
confidence: 99%
“…Twenty new studies were included in this update [26,27,28,29,31,38,39,40,44,45,47,49,50,53,59,61,66,67,79,81]. The language was predominantly English (96.7%).…”
Section: Resultsmentioning
confidence: 99%
“…Many countries have been trying to increase the accessibility to health care resources and provide better healthcare services for their people. Studies regarding the health inequality issue have found influences of racial/ethnic [1-3], socioeconomic [4,5] and geographic [6-8] factors on health status (e.g., disease status [5,9] or mortality [10,11]), healthcare resources utilization [8,12,13], and outcomes (e.g., postoperative mortality rates [14]). Most of the results from these studies have pointed to positive relationships between the indicators of social status and various health outcomes [15-17].…”
Section: Introductionmentioning
confidence: 99%